2022
DOI: 10.3390/ijerph19137697
|View full text |Cite
|
Sign up to set email alerts
|

Attitude towards Euthanasia among Medical Students: A Cross-Sectional Study in Hong Kong

Abstract: Background: With an increasing aging population and heavy medical burden, euthanasia has become a controversial topic in Hong Kong (HK) in recent years. Medical students are future medical professionals who may face novel and evolving ethical dilemmas. Hence, their views on euthanasia are crucial. Objective: To examine the attitudes of medical students towards euthanasia in HK and identify the factors associated with their attitude towards euthanasia. Methods: A questionnaire-based cross-sectional study among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Gender is also identified as a variable that affects attitude towards euthanasia. Male students showed positive response as compared to females; it is similar to a study conducted by Lau AM in Hong Kong 6 and another study by JC Penman 10 Possibly, gender can have a role in managing emotions, maintaining self-integrity, and helping patients while making decisions.…”
Section: Students' Corner Short Reportsupporting
confidence: 83%
See 1 more Smart Citation
“…Gender is also identified as a variable that affects attitude towards euthanasia. Male students showed positive response as compared to females; it is similar to a study conducted by Lau AM in Hong Kong 6 and another study by JC Penman 10 Possibly, gender can have a role in managing emotions, maintaining self-integrity, and helping patients while making decisions.…”
Section: Students' Corner Short Reportsupporting
confidence: 83%
“…In this study, 66% of students opposed euthanasia, which is consistent with results obtained in studies conducted at other medical universities in Pakistan. 5 This trend was also seen in a study conducted in Hong Kong, 6 although a contrast was seen in India 7 where acceptance of euthanasia was 61%.…”
Section: Students' Corner Short Reportmentioning
confidence: 77%
“…The results regarding the students' attitudes toward assisted suicide were divergent. In some studies, more students supported the legalisation of assisted suicide than that of euthanasia [16,34], and there are other studies in which less students supported assisted suicide than euthanasia [15,18]. In some countries, an indirect way of introducing euthanasia is a decriminalisation of assisted suicide [35].…”
Section: Discussionmentioning
confidence: 99%
“…The results of studies regarding medical students' attitudes toward euthanasia and assisted suicide suggest significant discrepancies, e.g., euthanasia and assisted suicide have proponents amounting to 24-97.4% and 13-69%, respectively [9][10][11][12][13][14][15][16]. There is more support for euthanasia in countries where it is legal, e.g., in Belgium 97.4% [17] and in Canada 88% [18], compared to countries where it is forbidden, e.g., in China 41.2% [15] and Germany 19.2% [16]. Factors that significantly impact negative attitudes toward euthanasia and assisted suicide comprise religion [11,19], a higher year of study [20,21], a lack of law acceptance and a concern for abuse [22].…”
Section: Introductionmentioning
confidence: 99%
“…2 Research has shown that nearly half of medical students hold a positive attitude toward euthanasia, with over a quarter supporting its legalization, even though it is strictly prohibited in many countries around the world. 3,4 This diversity in opinions reflects the need for a deeper understanding of medical students' attitudes toward euthanasia. Certainly, understanding the factors Article that shape individuals' attitudes toward euthanasia will be crucial for medical professionals, as it can influence their decision-making process and patient care.…”
Section: Introductionmentioning
confidence: 99%